2015
DOI: 10.1039/c4sc02705a
|View full text |Cite
|
Sign up to set email alerts
|

Electron localization in a mixed-valence diniobium benzene complex

Abstract: One electron oxidation of a neutral diniobium benzene complex leads to a mixed-valence species. Single crystal X-ray diffraction, EPR, L3,2-edge XANES, and DFT indicate that the unpaired electron is localized on one metal center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 62 publications
2
19
0
Order By: Relevance
“… 45 In the latter case, and contrary to what is observed for 2 , we observed that the two-electron oxidation is irreversible and the arene-bridged complex decomposes. 57 This difference in reactivity can be ascribed to a stronger interaction and stronger orbital overlap with the cyclo -P 4 ring vs C 6 H 6 . This is also consistent with the fact that benzene does not displace CO in the dicarbonyls [(BDI)(N t Bu)M(CO) 2 ] (M = Nb, Ta), while P 4 does.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 45 In the latter case, and contrary to what is observed for 2 , we observed that the two-electron oxidation is irreversible and the arene-bridged complex decomposes. 57 This difference in reactivity can be ascribed to a stronger interaction and stronger orbital overlap with the cyclo -P 4 ring vs C 6 H 6 . This is also consistent with the fact that benzene does not displace CO in the dicarbonyls [(BDI)(N t Bu)M(CO) 2 ] (M = Nb, Ta), while P 4 does.…”
Section: Resultsmentioning
confidence: 99%
“…This observation is in stark contrast to that of {[(BDI)(N t Bu)Nb] 2 (μ-C 6 H 6 )}{BAr F }, where the single electron is not delocalized equally onto both niobiums, resulting in a more complex EPR signal. 57 The more isotropic and equal distribution of the spin density in 5 suggests better orbital overlap.…”
Section: Resultsmentioning
confidence: 99%
“…A more pronounced example of bridging ligand modification is provided by the curious mixed‐valent compound obtained from a dinuclear niobium compound with an inverted sandwich structure in which niobium atoms are bridged by a benzene in a µ‐η 6 :η 6 way . The formal oxidation state of Nb can be defined as III (d 2 ).…”
Section: Some Original Structuresmentioning
confidence: 99%
“…58 Spectroscopic and crystallographic data were again consistent with a neutral bridging benzene molecule, and unlike 114, the dimeric structure of 122 readily broke up to generate monomeric Nb(III) and Nb(IV) + fragments which engaged in reactivity with a variety of substrates including THF to re-form 114 and give Nb(IV) cation 124, DCE to give Nb(V)-Nb(V) dimer 125, and t BuN 3 to give Nb(V) complexes 126 and 127. 58 Spectroscopic and crystallographic data were again consistent with a neutral bridging benzene molecule, and unlike 114, the dimeric structure of 122 readily broke up to generate monomeric Nb(III) and Nb(IV) + fragments which engaged in reactivity with a variety of substrates including THF to re-form 114 and give Nb(IV) cation 124, DCE to give Nb(V)-Nb(V) dimer 125, and t BuN 3 to give Nb(V) complexes 126 and 127.…”
Section: Scheme 27mentioning
confidence: 99%